A novel STIM1-Orai1 gating interface essential for CRAC channel activation. (May 2019) - Butorac, Carmen; Muik, Martin; Derler, Isabella; Stadlbauer, Michael; Lunz, Victoria; Krizova, Adéla; Lindinger, Sonja; Schober, Romana; Frischauf, Irene; Bhardwaj, Rajesh; Hediger, Matthias A.; Groschner, Klaus; et al.
Graphical abstract: Highlights: A short domain within the SOAR fragment of STIM1 is involved in transmitting the activation action of STIM1 to Orai1. This domain contributes to a STIM1-Orai1 gating interface, separating STIM1 coupling to Orai1 from gating of Orai1. The formation of a STIM1-Orai1 gating interface conveys a molecular trigger to elicit CRAC channel gating. Abstract: Calcium signalling through store-operated calcium (SOC) entry is of crucial importance for T-cell activation and the adaptive immune response. This entry occurs via the prototypic Ca 2+ release-activated Ca 2+ (CRAC) channel. STIM1, a key molecular component of this process, is located in the membrane of the endoplasmic reticulum (ER) and is initially activated upon Ca 2+ store depletion. This activation signal is transmitted to the plasma membrane via a direct physical interaction that takes place between STIM1 and the highly Ca 2+ -selective ion channel Orai1. The activation of STIM1 induces an extended cytosolic conformation. This, in turn, exposes the CAD/SOAR domain and leads to the formation of STIM1 oligomers. In this study, we focused on a small helical segment (STIM1 α3, aa 400–403), which is located within the CAD/SOAR domain. We determined this segment's specific functional role in terms of STIM1 activation and Orai1 gating. The STIM1 α3 domain appears not essential for STIM1 to interact with Orai1. Instead, it represents a key domain that conveys STIM1 interaction into Orai1 channel gating. The results of cysteine crosslinking experiments revealed the close proximity of STIM1 α3 to a region within Orai1, which was located at the cytosolic extension of transmembrane helix 3, forming a STIM1-Orai1 gating interface (SOGI). We suggest that the interplay between STIM1 α3 and Orai1 TM3 allows STIM1 coupling to be transmitted into physiological CRAC channel activation.